Dataset on insight into inhibition capacity of cyclic tetra-amino acid based compounds as efficient crystal structure of human insulin-degrading enzyme inhibitorsMendeley Data - Cecilia O. Akintayo; Abel Kolawole Oyebamiji; Arogundade Ibukun O; Adeniyi Adebayo; Sunday Adewale Akintelu; Samson Olusegun Afolabi; Oluwakemi Ebenezer (Data in Brief)
The biochemical evaluation of nine cyclopeptide derivatives were investigated using computational approaches. Key software in drug design and discovery (Spartan for optimization; Molecular operating environment (MOE) for induced fit docking; ADMETSar for pharmacokinetics; GROMACS for molecular dynamic simulation) were employed in this work. The optimization was accomplished using 6–31G* as basis set via Spartan 14 software while the optimized compounds were docked against human insulin-degrading enzyme (2WBY). The embedded features of the optimized compounds were accessible after optimization and they were observed and reported. Also, methyl (3S,9S,12S)-12-(1,3-dioxoisoindolin-2-yl)-9-(4-hydroxybenzyl)-5,8,11-trioxo-4,7,10-triaza-1(1,3)-benzenacyclotridecaphane-3-carboxylate (compound 1) proved to possess greater potential to inhibit human insulin-degrading enzyme (2WBY) than other examined compounds and the reference compound (Metformin). The pharmacokinetic evaluation of compound with highest binding affinity and reference compound were executed and reported. Also, other activity of the lead compound were explored using SwissTargetPrediction software and the outcome were observed and reported